Iron and Viking Age grapes from Denmark: vine seeds found at the royal complexes by Lake Tissø - Henriksen, Peter Steen; Holst, Sandie; Frei, Karin Margarita (Danish Journal of Archaeology, 2017)
Since the mid 1990s the National Museum of Denmark and Museum Vestsjælland have conducted excavations on two royal residential complexes from late Germanic Iron Age and Viking Age. During the excavations a range of samples were collected for macrofossil analysis. In two of these samples two seeds of vine grapes dated to the late Germanic Iron Age and the Viking Age were discovered. So far they are the oldest grape seeds discovered in the present Danish area. One of the seeds was chosen for strontium isotope analysis in order to determine the provenance of the grape. The strontium isotopic composition of the grape seed yielded a 87Sr/86Sr ratio of 0.71091 (±0.00004; 2σ) which falls within Denmark’s strontium isotopic baseline range indicating that the seed could be of local origin. Archaeological and historical evidence seem to point to that people in the Iron and Viking Age knew and consumed wine and even had access to gain potential know-how related to wine production. Hence, even though it is not possible to determine whether the two seeds found at Tissø are a result of either grape consumption (fresh or dried) or used for wine production, these finds point to that grapes and probably wine were products consumed by the elite at Tissø.